Bio-inspired self-stitching discontinuous fiber reinforced composites with enhanced ductility and energy absorption. (October 2022) - Ding, Zhongqiu; Duan, Yugang; Xiao, Hong; Wang, Ben
Abstract: This paper innovatively proposed a biomimetic self-stitching carbon fiber reinforced polymer (CFRP) with a unique microstructure of inter-laminar overlapping region inspired by the overlapping feature of ironclad beetle and brick-and-mortar feature of nacre. To investigate the effectiveness of self-stitching microstructure, two baseline configurations of continuous unidirectional CFRP and discontinuous staggered CFRP were designed. Three-point bending tests showed that the self-stitching microstructure can significantly enhance the pseudo-ductility of CFRP composite by inhibiting crack propagation through additional fiber bridging. In addition, varying the overlap length can also result in different mechanical responses and failure modes. Compared to unidirectional CFRP, the self-stitching CFRP with a well-designed discontinuity at the ply level can improve failure strain and energy absorption by more than 228% and 85%, respectively. Graphical abstract: Image 1 Highlights: A novel biomimetic self-stitching CFRP with a unique microstructure of inter-laminar overlapping region was proposed. The first CFRP composite with self-stitching microstructure was prototyped. The unique large-scale bridging phenomenon of self-stitching CFRP inhibited crack propagation. The self-stitching CFRP with optimal step length attained extraordinary pseudo-ductility and energy absorption.